Peningkatan Pendapatan Melalui Pengelolaan Bernilai Tambah pada Usaha Rumahan - Ida Ayu Kade Rachmawati Kusasih; Budi Istiyanto (JPPM (Jurnal Pengabdian dan Pemberdayaan Masyarakat), 2017)
The role of a wife has begun to shift into an entrepreneur now. This starts with a home-based business that was initially done to fill the spare time after the housekeeping duty were completed. But in managing the business they are still simple oriented just to fill the time, so that this business is not able to develop properly. This dedication seeks to empower the home-based business to be able to have added value that previously only runs with many limitations. Implementation of community service program on partner 1 (Arum Snack) by giving peanut slicer to save time to make sliced peanut so that productivity will increase. Likewise with the financial management that has been separating business finances with the family though still manually using a cash book.For partner 2 (Yasmin Collection) already has blogs and facebook to expand its online marketing range. An online address created by the name Yasmin Online Shop that shifts from fashion sales goes to typical Klaten snacks produced by home-based production around partners. The products is Marketed to outside Java, especially Kalimantan although that is still limited.Monitoring and evaluation on activities and mentoring program are still done. The addition of brand on partner products is also done so that the products can be more marketable. Simple financial management assistance is done so that partners can access loans from financial institutions to increase their working capital.Increased revenue in this program is achieved on all of the partners. Suggestion that can be given is  more attention from the governments in the development of home-based businesses involving academics.  Keyword : revenue increase, home business